Gene Expression Signatures and Response to Imatinib Mesylate in Gastrointestinal Stromal Tumor - Rink, Lori (2009)
PURPOSE: Despite initial efficacy of imatinib mesylate (IM) in most gastrointestinal stromal tumor (GIST) patients, many experience primary/secondary drug resistance. Therefore, clinical management of GIST may benefit from further molecular characterization of tumors before and after IM treatment. EXPERIMENTAL DESIGN: As part of a recent Phase II Trial of neoadjuvant/adjuvant IM treatment for advanced primary and recurrent operable GISTs (RTOG-S0132), gene expression profiling using oligonucleotide microarrays was performed on tumor samples obtained before and after IM therapy. Patients were classified according to changes in tumor size after treatment based on CT scan measurements. Gene profiling data were evaluated with Statistical Analysis of Microarrays (SAM) to identify differentially expressed genes (in pre-treatment GIST samples). RESULTS: Based on SAM (FDR=10%), thirty-eight genes were expressed at significantly lower levels in the pre-treatment biopsy samples from tumors that significantly responded to 8 to 12 weeks of IM, i.e., ≥25% tumor reduction. Eighteen of these genes encoded KRAB domain containing zinc finger (KRAB-ZNF) transcriptional repressors. Importantly, ten KRAB-ZNF genes mapped to a single locus on chromosome 19p, and a subset predicted likely response to IM-based therapy in a naïve panel of GISTs. Furthermore, we found that modifying expression of genes within this predictive signature can enhance the sensitivity of GIST cells to IM. CONCLUSIONS: Using clinical pre-treatment biopsy samples from a prospective neoadjuvant phase II trial we have identified a gene signature that includes KRAB-ZNF 91 subfamily members that may be both predictive of and functionally associated with likely response to short term IM treatment.